PENINGKATAN PELAYANAN PUBLIK MELALUI SISTEM INFORMASI KAMPUNG CIBOLANG DESA TELUK PINANG - virly, Neng; Pratidina, Ginung; Novando, Novando; Maulinda, Winda; Putri, Yunita Sugiawan; Apriani, Winda (DEVOSI, 2024)
Government programs and services have problems identified including protracted delays, requests for rewards, not providing services, incompetence, abuse of authority, discrimination, and partiality. Community service in Telukpinang Village, Ciawi District, Bogor Regency by Fisip Djuanda University aims to improve public services through the utilization of information technology, specifically the Cibolang Village Information System of Teluk Pinang Village (SIKANCIL TENANG). This activity includes observation, preparation, pretest and posttest, as well as training and counseling involving all village employees. The observation results showed that the village had not maximized information technology for public services. The pretest results showed that the participants' knowledge was quite good with an average of 62%, but after the training, the participants' knowledge increased to 88%. The materials presented included the concept of public services, legal basis, service standards, and components of public service standards, as well as the operational use of SIKANCIL TENANG.  This information system is designed to simplify population administration and improve the efficiency of village services. The training results showed a significant increase in participants' understanding, as evidenced by higher posttest results compared to the pretest. The use of SIKANCIL TENANG is expected to provide more efficient, faster, and transparent public services, thereby increasing public trust in the village government. The implementation of this technology also aims to reduce inequality and create a conducive environment for investment as well as equitable services in various aspects, including education and health.